Legality of Ownership of Asteroid Mining Results in Space Based on International Law Arrangements - Spears, Laura; Martin, John; Rotham, Betty (Pancasila International Journal of Applied Social Science, 2023)
Asteroid mining is a proposed solution for mining elements that are commonly obtained from conventional mining as we know it today. However, until now there are no Indonesian laws and regulations, nor international agreements that directly regulate what rights miners of space resources will have. Without certainty about what property rights exist in extracted resources, the incentives to extract these resources will be greatly reduced. The research method in this journal uses a statutory approach, examining the statutory regulations concerned with the legal issues raised, and a conceptual approach, namely an approach based on legal concepts related to the legal issues at issue. Based on the facts found, it can be concluded that the concept of property rights exists and is recognized in the space law regime, even in the absence of territorial rights over celestial bodies, although its application to resource extraction remains a contentious issue.